2020
DOI: 10.9734/jsrr/2020/v26i330231
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biogas and Biofertilizer Production from Anaerobic Codigestion of Harvest Residues and Goat Manure

Abstract: Comparative assays were conducted to assess the biogas and biofertilizer production efficiency from anaerobically codigested goat manure (GM) and harvest residues: corn stover (CS) and rice straw (RS). All digesters were operated simultaneously under mesophilic temperature of 40°C and notable phosphate solubilizing and nitrogen fixing bacterial populations indicated qualitative biofertilizer quality of the digestates. Codigestion of the substrates significantly increased biogas yield (p < 0.05) compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The total solids contents obtained in the study were generally considered appropriate for dry AD at high solid content (Motte et al, 2013). Comparable degradation in the TS and VS contents during anaerobic digestion have been documented in previous literature (Ndubuisi-Nnaji et al, 2021, Ndubuisi-Nnaji et al, 2020b, Lu, et al, 2016Qi et al, 2018;Panjicko et al, 2015).…”
Section: Results and Discussion Biomethane Potential Of Poultry And G...supporting
confidence: 60%
“…The total solids contents obtained in the study were generally considered appropriate for dry AD at high solid content (Motte et al, 2013). Comparable degradation in the TS and VS contents during anaerobic digestion have been documented in previous literature (Ndubuisi-Nnaji et al, 2021, Ndubuisi-Nnaji et al, 2020b, Lu, et al, 2016Qi et al, 2018;Panjicko et al, 2015).…”
Section: Results and Discussion Biomethane Potential Of Poultry And G...supporting
confidence: 60%
“…The cumulative biomethane yield from mono-and-codigestions of GM and CGT at the end of BMP assays is shown in There are no reports of anaerobic digestion of GM with CGT to date. However, previous studies have reported the biomethane potential of GM with other agricultural wastes such as wheat straw (WS), corn stalks (CS), and rice straw (RS) [40,53] swine, and dairy cow manure [23,27]. Zhang et al [52] reported biomethane yields of 225.5, 261.6, 331.2, and 324.3 mL/g vs from 55 days of GM mono-digestion and co-digestions having missing ratios of GM/WS 30:70, GM/CS; 70:30, and GM/RS; 50:50, respectively, under mesophilic conditions.…”
Section: Cumulative Biomethane Production and Biodegradabilitymentioning
confidence: 99%
“…Lignocellulosic agro-wastes comprising coconut husk fiber, pineapple floret and banana stem are abundant in nature and can serve as alternative yet sustainable energy sources. At present, anaerobic digestion (AD) has extensively been employed in the treatment and management of most biodegradable waste, namely: harvest residues, animal manures, municipal sewage sludge and kitchen waste [1]. Lab-scale anaerobic codigestion of lignocellulosic biomass has been studied in recent times [2], [3].…”
Section: Introductionmentioning
confidence: 99%